A genome-wide association study on hematopoietic stem cell transplantation reveals novel genomic loci associated with transplant outcomes - Rosenberger, Albert; Crossland, Rachel E.; Dressel, Ralf; Kube, Dieter; Wolff, Daniel; Wulf, Gerald; Bickeböller, Heike; Dickinson, Anne; Holler, Ernst (Frontiers in Immunology, 2024)
Introduction Data on genomic susceptibility for adverse outcomes after hematopoietic stem cell transplantation (HSCT) for recipients are scarce. Methods We performed a genome wide association study (GWAS) to identify genes associated with survival/mortality, relapse, and severe graft-versus-host disease (sGvHD), fitting proportional hazard and subdistributional models to data of n=1,392 recipients of European ancestry from three centres. Results The single nucleotide polymorphism (SNP) rs17154454, intronic to the neuronal growth guidant semaphorin 3C gene (SEMA3C), was genome-wide significantly associated with event-free survival (p=7.0x10-8) and sGvHD (p=7.5x10-8). Further associations were detected for SNPs in the Paxillin gene (PXN) with death without prior relapse or sGvHD, as well as for SNPs of the Plasmacytoma Variant Translocation 1 gene (PVT1, a long non-coding RNA gene), the Melanocortin 5 Receptor (MC5R) gene and the WW Domain Containing Oxidoreductase gene (WWOX), all associated with the occurrence of sGvHD. Functional considerations support the observed associations. Discussion Thus, new genes were identified, potentially influencing the outcome of HSCT.